Comparative analysis of microgaps in angled and straight components: a laboratory study - Lobo, Yuri Lins; Mendes, Giovanna Nascimento; Santana, Lucas Alves da Mota; Floresta, Lara Gois; Marqueti, Antônio Carlos; Takeshita, Wilton Mitsunari [UNESP]; Trento, Cleverson Luciano (My University, 2024)
Introduction: The dental implant rehabilitation protocol is a well-established treatment option for edentulous patients with a high success rate. However, there are factors that can lead to difficulty in continuation and even complete loss of rehabilitation. Microgaps are spaces found between the implant and prosthetic abutment that are caused by the limit of precision in the manufacturing of the implant. This space can cause micromovements and bacterial microleakage that can compromise the long-term useful life of the implant. Objective: Measure and evaluate microgaps in angled and straight implants using scanning electron microscopy. To carry out the study, a total of 30 SIN® osseointegrated implants were used, 15 of which were straight and 15 angled. Material and method: For the comparative analysis of these components, scanning electron microscopy was used, carried out by a properly calibrated and experienced researcher. Result: It was observed that the microgap measurements of both components are in accordance with the clinically acceptable values presented in the literature, however the microgap values of the angled components were considerably higher compared to the straight components. Conclusion: Although the values presented corroborate the data presented in the literature, additional studies are necessary for a more comprehensive and in-depth understanding of the relationship between the microgaps of the morse cone system components.
Análise comparativa de microgaps em componentes angulares e retos: um estudo de laboratório
Keywords: dental implant-abutment design; Dental implants; dentistry